CancerNet – web site that gives an access to the database of National Cancer Institute of USA - Mackiewicz, Małgorzata; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2000)
The CancerNet www – site gives an access to databases of National Cancer Institute, Bethesda USA. Using nine main links we can find information concerning ongoing and already closed clinical trials (for ex. 1 800 phase I and 10 500 phase II trails), diagnostic procedures as well as genetic background of cancer. There is a possibility of submission to National Cancer Institute of your own clinical trial protocols, which will be subsequently available through CancerNet web-site. A very important feature is a direct access to a bibliographic database – CANCERLIT &reg ;, which has been collecting information on oncological literature since early ‘60.